The four W: participative communication strategy in Bugel urban village, Salatiga - Rini Darmastuti; Dian Novita Kristiyani; Sri Winarso; Erwin Christianto; Birmanti Setya Utami (Jurnal Studi Komunikasi, 2024)
Community development has shifted from short-term, top-down programs to community empowerment programs that are deeply rooted in the community, as a result, the communication strategies used have also changed. The purpose of this paper is to describe the participative communication model for community empowerment in Bugel Urban Village, Salatiga. This paper is based on the results of research conducted using Bugel Urban Village, Salatigawere collected through in-depth interviews, observation, and focus group discussions. Data analysis was conducted using qualitative analysis. The results of this study are first, Bugel Urban Village has health facilities, education, culture, arts, MSMEs, and tourist attractions that have potential for regional development. Second, the communication strategy that can be used to empower the Bugel community is a communication strategy with an informal approach that emphasises community participation. Third, the communication model for community empowerment in Bugel Urban Village is a participative communication model with a 4W approach (wangun, waras, wareg and wasis). It is urgent to apply these findings, because the 4W approach focuses on structure, health, satisfaction, and wisdom can be used as a reference for participative communication models for communities in Bugel Urban Village, Salatiga.